HALAL CERTIFICATION GUARANTEE AS A CONSUMER PROTECTION EFFORTS - Wahyudi, Dian; Zaka, Kurnia Putra (Journal of Islamic Economic Scholar, 2020)
The purpose of this study is to determine the halal certification guarantee in national law and the MUI fatwa system along with the halal labeling registration procedure as an effort to protect consumers with a normative juridical approach. Halal certificate is halal recognition of a product issued by BPJPH based on MUI written fatwa and becomes a compulsory foundation source for companies / communities in accordance with Law Number 33 of 2014 concerning Halal Product Guarantee, Act Number 8 of 1999 concerning Consumer Protection.Keywords: guarantee, Halal Certification, Consumer Protection,